Diseño de una canteadora para madera de cuatro cuchillas con sistema de chumaceras para la “Ebanistería hermanos congo”, en la ciudad de Quevedo, año 2015 - Congo Cervantes, Jorge Luis (2015)
The following present work of qualification, it addresses on the work of wood give a better finish in the furniture making process. Focusing the development of new technologies with a view to improving the craft, which is summarized in seven chapters: Chapter 1, supports research, considering the need to purchase new equipment for the carving of wood with better technologies. Routing the objectives to the design of this machine, in such a way, is justified now craft workshops have a low performance with existing machines. Chapter 2, describes concepts and terms used in the carving of wood, as also the functioning of the mechanical elements of the Edger. Chapter 3, discusses the location of deployed to this design, with the respective research methodology is to adopt an experimental design, which sets the effect from the operation of the edging machine. Chapter 4, the purpose of the study of field, is in order to determine the parameters and requirements of designs of mechanical elements. In addition are the respective analyses performed in Mdsolids, Autocad and Solidworks software. The determination of an economic study demonstrates that to implement this design, the execution is viable. Ending with the respective discussion, where they have enhance the conclusions and corresponding recommendations. Chapter 5, conclusions and recommendations which are reflected the observations made during the investigation. Chapter 6 and 7, detailed bibliography which made possible the research and annexes respectively.